MEKANISME FATIK DAN PENGARUH RESONANSI PADA KERUNTUHAN JEMBATAN CALLENDER HAMILTON - Tristanto, Lanneke (Jurnal Jalan Jembatan, 2018)
The complication in fatique mechanism of bridges is becoming transparent through simplified basic knowledge principals. Bridges are subjected to self weight and vehicle traffic loads, causing structural deformation throughout the life time. Deformation causes stress in the bridge material. Material stress capacity is the source for bridge strength. The bridge strength that is optimal during servicability life, decreases in time of maintenance, and becomes fatique in time of replacement. Fatique mechanism is high lighted in bridge failure cases. Fatique of material needs a long process before developing into total damage, therefore a bridge structure will not collapse due to fatique conditions only. During traffic jams, resonance will occur between the heavy vehicles as vibration machine (frequency 2-3 Hertz) and steel truss girder (frequency 2-3 Hertz). Resonance between two identical frequency vibrations increases the bridge response to infinite displacement, causing a sudden failure like in an earthquake disaster. Key words : fatique, resonance, frequency, displacement